Understanding of the role of digitalization to business model and innovation: economics and business review studies - Hendriarto, Prasetyono (Linguistics and Culture Review, 2021)
This paper analyzed the role of the digitalization approach in innovating business operating models in Indonesia. We chose a review research approach on the findings of economic and business journals that we searched electronically based on Google application data. We focus on findings from international journals that discuss how digitalization plays a role in innovation models of profitable and sustainable business operations. We reviewed papers published in the last ten years (2010 to 2020) using data analysis, critical evaluation, and in-depth interpretation methods to find valid and reliable data. Our analysis focuses on business innovation models operating with digital services; production, distribution, and sales. We found that the role, implementation, and activities of digital applications in business are proven to overcome obstacles to business operations in the current multi-crisis and pandemic era. In other words, the digitalization trend has proven to be very helpful for operational business processes that follow an adaptation approach to the demands of technological convenience by companies and consumers. Furthermore, we believe that business innovation with a digitalization approach is an effort to improve services in all operational lines to achieve profitable and sustainable business goals.